Social recourse for grabbed property : the widows’ experiences in Binga district, Zimbabwe - Dube, Misheck (Penerbit Universiti Kebangsaan Malaysia, 2019)
Grabbing property from the widows is a huge social problem in Zimbabwe. Despite recent changes and advances in policy frameworks in the country, once the husband dies, a widow still struggles to inherit the property accrued during the time of marriage irrespective of the kind of marriage entered into with the late husband. This paper discusses formal and informal social recourse experiences of the widows for grabbed property in Binga District in Zimbabwe. A qualitative research approach was adopted which purposely engaged ten widows in in-depth face-to-face interviews to gather their experiences on recourse. The results indicated that a few widows attempted locally available social recourse for grabbed property whilst many widows suffered in silence and never attempted to seek any recourse owing to various social and cultural reasons and expectations. Formal and informal locally available interventions have been found to have little significance as recourse for grabbed property. This state of affairs has proved to have dire psychosocial and socioeconomic consequences for widows and well-structured interventions proved vehemently needed. The conclusion was that locally available interventions for grabbed property were less viable social recourse measures for widows and did not serve to regain their lost property. This paper recommends the need for social work intervention at various levels to ameliorate the plight of widows in Binga District in Zimbabwe.